Середньовічні археологічні пам’ятки у Судовій Вишні на Львівщині: історія та перспективи дослідження - Терський, Святослав (Publishing House of Lviv Polytechnic National University, 2015)
Проаналізовано введення у науковий обіг результатів археологічних досліджень 1956–1962 рр. у Судовій Вишні на Львівщині, а також доля археологічних знахідок, здобутих на цих пам’ятках дослідженнями відомого українського археолога Олексія Ратича. Обґрунтовано висновок про важливу роль цих матеріалів для з’ясування етнокультурних процесів на Східному Прикарпатті у X–XI ст. One of the best studied monuments of X–XI centuries. in the Eastern Carpathian region is in settlement Zamchysko, which occupies the edge of a high ridge on the western outskirts of town Sudova Vyshnia. The article analyzes the process of scientific research of the results of archaeological investigations 1956–1962 biennium of archaeological monuments of town Sudova Vyshnia in court in Lviv, and the fate of archaeological findings obtained in research on these monuments famous Ukrainian archaeologist Olexii Ratycz. The main stages of the study of this monument linked to one of the founders of postwar Lviv archaeological school Olexii Ratycz. Within six field seasons scientist managed to explore the most central part of the monument. Scientists gained invaluable scientific material gave evidence to determine the merits of ethnocultural processes in the Eastern Carpathian region in X–XI centuries. It was published in almost ten short articles and reports written by excavation. For over half a century of research data cannot fully published. The history of the publication of these scientific achievements has sometimes detective character. However, the weight of the scientific findings of the excavations Olexii Ratycz periodically attracts many scientists in connection with the study of various aspects of the history and archaeology of Ukrainian lands. This study is the first modern attempt to generalize about the stages and the results of research systems early medieval monuments located on the basin of Vyshnia river in Lviv region.
Keywords: археологічні знахідки; фондові колекції; музеї; Судова Вишня; городища; Олексій Ратич; archaeological finds; fund collections; museums; Sudova Vyshnia; old castles; Olexii Ratycz